The influence of Temperature and Vacuum Pressure on Water Vaporization, Volume Changes and Density Ratio of Fruit Chips During Vacuum Frying - Jamaludin, Jamaludin; Suardy, Suardy; Siswantor, Siswantor; Laga, Suriana (Fakultas Teknologi Pertanian Universitas Brawijaya, 2011)
During vacuum frying process of product (fruit), simultanous heat and masstransfers occur. Heat transfer from hot oil to product surface, and into product causeswater to evaporate. This makes changes of volume and density ratio of fried products.This research aims to investigate the infulence of water vaporization on volume anddensity ratio changes of product during vacuum frying process. The samples are jackfruits fried at temperature of 90 and 100OC with frying duration of 15-16 minutes atvacuum pressure of 10 and 15 kPa (absolute pressure). All water in products isassumed to be free water causing shrinkage and puffing, and also decreasing andincreasing of product pores, if the water is removed. The observed parameters areÂ water vaporization of volume and density ratio change. The result showed thattemperature and vacuum pressure influenced water vaporization, volume change, anddensity ratio of product. The rate of volume and density ratio changes were affected byrate of water vaporization. If the water vaporization was not stable yet, decreasing andincreasing of pores occurred. After being stable, puffing and pore increasing started tooccur untill the end of frying.Keywords: temperature, vacuum pressure, water content, volume and porousity